Transesterification of palm oil to biodiesel by using waste obtuse horn shell-derived CaO catalyst - Lee, Seik Lih; Wong, Yong Chen; Tan, Yen Ping; Yew, Sook Yan (Elsevier, 2015)
The calcium oxide catalysts derived from waste obtuse horn shells were utilized in the transesterification of palm oil into biodiesel. This environment-friendly catalyst is thermally activated at 800 °C for 3 h. The resulting CaO catalyst was characterized using thermogravimetric analysis (TGA), X-ray diffraction (XRD), temperature-programmed desorption of CO2 (TPD-CO2), Brunauer–Emmett–Teller (BET) surface area analysis, and scanning electron microscopy (SEM). XRD patterns of calcined catalyst showed intense peaks of calcium oxide, consistent with XRF results that revealed calcium is the major element present in the obtuse horn shells. High calcination temperature (800 °C) tended to promote agglomeration of fine crystals, resulted in a smaller surface area (0.07 m2/g) as examined by BET. Catalytic activities in the transesterification process had been investigated using one-variable-at-a-time technique. The optimum palm oil conversion was 86.75% under reaction conditions of 6 h, 5 wt.% of catalyst amount and methanol to oil ratio of 12:1. Reusability of this waste shell derived catalyst was examined and results showed that the prepared catalysts are able to be reused up to 3 times with conversion of more than 70% after the third cycles. Although the reusability may not be excellent at the moment, it is still in the exploratory study. More efforts were done to improve its properties and stability.